Dialética da diferença - Bueno, Sinésio Ferraz [UNESP] (My University, 2013)
The present article aims to discuss the theme of dialectical difference according to the concepts of critical theory. At first, the issue of the difference will be thinking about their negative reception that the production of stereotypes and prejudices on ethnicity, race and gender. In a second step, the subject will be treated on its positive reception, very common among social movements and leftist academic. In a third step, both types receive the difference will be problematized from the thought of Theodor Adorno in his Negative Dialectics as possible from mediation between universality and particularity empirical conceptual.

O presente artigo tem por objetivo problematizar dialeticamente o tema da diferença de acordo com os conceitos da teoria crítica. Em um primeiro momento, o tema da diferença será pensado em sua recepção negativa referida à produção de estereótipos e preconceitos de natureza étnica, racial e de gênero. Em um segundo momento, o tema será tratado em sua recepção positiva, muito comum entre movimentos sociais de esquerda e meios acadêmicos. Em um terceiro momento, ambos os tipos de recepção da diferença serão problematizados a partir do pensamento de Theodor Adorno, em sua Dialética negativa, como possível via de mediação entre a particularidade empírica e a universalidade conceitual.